Urinary retention following transperineal template prostate biopsy – study of risk factors. (January 2013) - Willis, Susan; Bott, Simon; Montgomery, Bruce
Background: As greater numbers of transperineal template prostate biopsies (TTPBs) are being performed, we have noticed that a considerable number of patients experience urinary retention post-procedure. We wanted to quantify this, and to examine factors that might predict which patients will experience retention. Patients and methods: Data analysis was performed on a prospectively maintained database on 93 consecutive patients undergoing template prostate biopsy over a 12-month period. Results: Mean patient age was 66 years (range 46–79). Mean prostate-specific antigen (PSA) was 8.34 ng/ml (1–31), mean transrectal ultrasonography (TRUS) volume 51 cc (10–133) and mean number of cores 52 (11–84). Twenty-five patients had muscle relaxant as part of their anaesthetic (27%). Fifteen patients had haematuria immediately post-procedure (16%). Twenty-six procedures were performed by a urology trainee (28%). Sixteen patients experienced retention post-template biopsy (17%). Their mean age was 67 years, mean PSA 8.9 ng/ml, mean TRUS volume 68 cc and mean number of cores 58. Of the retention group, 10 patients had muscle relaxant (63%), one patient had haematuria (6%) and four procedures were performed by a trainee (25%). Factors that significantly correlated with retention were TRUS volume ( r = 0.36, p = 0.0004) and the use of muscle relaxant ( r = 0.37, p = 0.0003). Age, PSA, number of cores taken, haematuria post-biopsy, and intra-operative furosemide, paracetamol, diclofenac, morphine and dexamethasone were not correlated with retention ( p > 0.05). Conclusion: Patients with higher TRUS volumes are at increased risk of retention post-TTPB and should be counselled accordingly. Due to anti-muscarinic effects, muscle relaxants should not be used.